Integer-valued self-exciting threshold autoregressive processes - Monteiro, M. (2012)
In this article, we introduce a class of self-exciting threshold integer-valued autoregressive models driven by independent Poisson-distributed random variables. Basic probabilistic and statistical properties of this class of models are discussed. Moreover, parameter estimation is also addressed. Specifically, the methods of estimation under analysis are the least squares-type and likelihood-based ones. Their performance is compared through a simulation study. Copyright © 2012 Taylor and Francis Group, LLC.